Understanding what young people know: methodological and theoretical challenges in researching young people's knowledge and understanding of the Holocaust. Issue 3 (3rd July 2017) - Chapman, Arthur; Hale, Rebecca
ABSTRACT: This article draws on research into young people's knowledge and understanding of the Holocaust conducted by the UCL Centre for Holocaust Education (CfHE). Two questions are addressed: "How can we theorize and measure development and progression in young people's historical knowledge and understanding of the Holocaust?" and "How can empirical social scientific research methods be used to help us describe young people's knowledge and understanding of the Holocaust?" This article reviews methodologies developed by the CfHE and exemplifies a research tool and two complementary approaches to analysis, focused on young people's descriptions of the Holocaust.